x⁴ + x = 0
x(x³) + x(1) = 0
x(x³ + 1) = 0
x = 0 or x³ + 1 = 0
- 1 - 1
x³ = -1
x = -1
Yes it does because when u multiply 2 negative you get a positive but since your adding another negative it goes back to a negative
You would do three square in length and 31 in width
The answer is (-2,-4) to solve this you need to add the X’s and divide by 2 and that will be your X for the midpoint, you do the same with the Y’s to find the y for your midpoint
Answer:
3
Step-by-step explanation:
find value at 12 =12
find value at 10 = 6
so it changes + 6 for a change from 10 to 12
6/2 = 3